Genome-wide simple sequence repeat markers in potato: abundance, distribution, composition, and polymorphism. (5th October 2021) - Jian, Yinqiao; Yan, Wenyuan; Xu, Jianfei; Duan, Shaoguang; Li, Guangcun; Jin, Liping
Abstract: Simple sequence repeats (SSRs) are important sources of genetic diversity and are widely used as markers in genetics and molecular breeding. In this study, we examined four potato genomes of DM1-3 516 R44 (DM) from S olanum phureja, RH89039-16 (RH) from Solanum tuberosum, M6 from Solanum chacoense and Solanum commersonii to determine SSR abundance and distribution and develop a larger list of polymorphic markers for a potentially wide range of uses for the potato community. A total of 1, 734, 619 SSRs were identified across the four genomes with an average of 433, 655 SSRs per genome and 2.31kb per SSR. The most abundant repeat units for mono-, di-, tri-, and tetra-nucleotide SSRs were (A/T)n, (AT/AT)n, (AAT/ATT)n, and (ATAT/ATAT)n, respectively. The SSRs were most abundant (78.79%) in intergenic regions and least abundant (3.68%) in untranslated regions. On average, 168, 069 SSRs with unique flanking sequences were identified in the four genomes. Further, we identified 16, 245 polymorphic SSR markers among the four genomes. Experimental validation confirmed 99.69% of tested markers could generate target bands. The high-density potato SSR markers developed in this study will undoubtedly facilitate the application of SSR markers for genetic research and marker-pyramiding in potato breeding.